A novel organ culture model of a joint for the evaluation of static and dynamic load on articular cartilage. Issue 3 (March 2018) - Lin, Y-C.; Hall, A. C.; Simpson, A. H. R. W.
Abstract : Objectives: The purpose of this study was to create a novel ex vivo organ culture model for evaluating the effects of static and dynamic load on cartilage. Methods: The metatarsophalangeal joints of 12 fresh cadaveric bovine feet were skinned and dissected aseptically, and cultured for up to four weeks. Dynamic movement was applied using a custom-made machine on six joints, with the others cultured under static conditions. Chondrocyte viability and matrix glycosaminoglycan (GAG) content were evaluated by the cell viability probes, 5-chloromethylfluorescein diacetate (CMFDA) and propidium iodide (PI), and dimethylmethylene blue (DMMB) assay, respectively. Results: Chondrocyte viability in the static model decreased significantly from 89.9% (sd 2.5%) (Day 0) to 66.5% (sd 13.1%) (Day 28), 94.7% (sd 1.1%) to 80. 9% (sd 5.8%) and 80.1% (sd 3.0%) to 46.9% (sd 8.5%) in the superficial quarter, central half and deep quarter of cartilage, respectively (p < 0.001 in each zone; one-way analysis of variance). The GAG content decreased significantly from 6.01 μg/mg (sd 0.06) (Day 0) to 4.71 μg/mg (sd 0.06) (Day 28) (p < 0.001; one-way analysis of variance). However, with dynamic movement, chondrocyte viability and GAG content were maintained at the Day 0 level over the four-week period without a significant change (chondrocyte viability: 92.0% (sd 4.0%) (Day 0) to 89.9% (sd 0.2%) (Day 28), 93.1% (sd 1.5%) to 93.8% (sd 0.9%) and 85.6% (sd 0.8%) to 84.0% (sd 2.9%) in the three corresponding zones; GAG content: 6.18 μg/mg (sd 0.15) (Day 0) to 6.06 μg/mg (sd 0.09) (Day 28)). Conclusion: Dynamic joint movement maintained chondrocyte viability and cartilage GAG content. This long-term whole joint culture model could be of value in providing a more natural and controlled platform for investigating the influence of joint movement on articular cartilage, and for evaluating novel therapies for cartilage repair. Cite this article : Y-C. Lin, A. C. Hall, A. H. R. W. Simpson. A novel organ culture model of a joint for the evaluation of static and dynamic load on articular cartilage. Bone Joint Res 2018;7:205–212. DOI: 10.1302/2046-3758.73.BJR-2017-0320.